Enhanced quantum state swapping via environmental memory - K. Mui; A. Couvertier; T. Yu (APL Quantum)
Environmental noise is a prevalent issue that hinders the widespread adoption of quantum technologies. Standard practice to mitigate noise involves minimizing the coupling between a quantum system and its environment, which is usually modeled in the Markovian regime. By moving slightly beyond this regime into the weak non-Markovian regime, we can achieve an effective coupling that is multiple orders of magnitude smaller by exploiting the environmental memory effect. To demonstrate this effect, we simulate state swapping in a Markovian and non-Markovian environment between two modes: a cavity mode initialized as a vacuum state and an atomic motional mode initialized as a displaced squeezed coherent state. To measure the quality of state swapping between environments, we calculate and compare their corresponding multi-mode fidelity for Gaussian states. We find that a non-Markovian environment has superior state swapping fidelity across the following parameters: mean phonon number, cavity decay rate, and vibrational frequency of the atomic motional mode. The fidelity is near-unit for a non-Markovian environment within the parameter ranges mentioned in the results. These results could enable enhanced quantum information exchange between a network and chain of cavity-atom nodes and contribute toward a more prevalent adoption of quantum technologies.